Genotypic Characterization of Clinical Klebsiella spp. Isolates Collected From Patients With Suspected Community-Onset Sepsis, Sweden - Saxenborn, Patricia; Baxter, John; Tilevik, Andreas; Fagerlind, Magnus; Dyrkell, Fredrik; Pernestig, Anna-Karin; Enroth, Helena; Tilevik, Diana (Frontiers in Microbiology, 2021)
Klebsiella is a genus of Gram-negative bacteria known to be opportunistic pathogens that may cause a variety of infections in humans. Highly drug-resistant Klebsiella species, especially K. pneumoniae, have emerged rapidly and are becoming a major concern in clinical management. Although K. pneumoniae is considered the most important pathogen within the genus, the true clinical significance of the other species is likely underrecognized due to the inability of conventional microbiological methods to distinguish between the species leading to high rates of misidentification. Bacterial whole-genome sequencing enables precise species identification and characterization that other technologies do not allow. Herein, we have characterized the diversity and traits of Klebsiella spp. in community-onset infections by whole-genome sequencing of clinical isolates (n=105) collected during a prospective sepsis study in Sweden. The sequencing revealed that 32 of the 82 isolates (39.0%) initially identified as K. pneumoniae with routine microbiological methods based on cultures followed by MALDI-TOF MS had been misidentified. Of these, 23 were identified as K. variicola and nine as other members of the K. pneumoniae complex. Comparisons of the number of resistance genes showed that significantly fewer resistance genes were detected in K. oxytoca compared to K. pneumoniae and K. variicola (both p-values <0.001). Moreover, a high proportion of the isolates within the K. pneumoniae complex were predicted to be genotypically multidrug-resistant (79/84, 94.0%) in contrast to K. oxytoca (3/16, 18.8%) and K. michiganensis (0/4, 0.0%). All isolates predicted as genotypically multidrug-resistant were found to harbor the combination of β-lactam, fosfomycin and quinolone resistance markers. Multi-locus sequence typing revealed a high diversity of sequence types among the Klebsiella spp. with ST14 (10.0%) and ST5429 (10.0%) as the most prevalent ones for K. pneumoniae, ST146 for K. variicola (12.0%) and ST176 for K. oxytoca (25.0%). In conclusion, the results from this study highlight the importance of using high-resolution genotypic methods for identification and characterization of clinical Klebsiella spp. isolates. Our findings indicate that infections caused by other members of the K. pneumoniae complex than K. pneumoniae are a more common clinical problem than previously described, mainly due to high rates of misidentifications.